BINARY SYSTEM OF CaO-P2O5 AS A BASIS OF MATERIALS FOR CORELATION OF SHELLET DISCHARGE - , С. П. (Municipal economy of cities. Series: «Economy science», 2018)
The prospects for the use of synthetic nanocrystalline materials of a multivariate composition based on the system СаО–P2О5–Н2О and additives for correcting structural defects of the skeleton are considered. It is shown that for the synthesis of nanocrystalline powders and composites of biomedical use, materials whose compositions are described by the system СаО–P2О5 are promising. The system of СаО–P2О5 wаs studied. The experimental verification of the polymorphism of Ca3(PO4)2 is carried out. The experimental verification of the calculated data on the preparations of the calculated compositions by the high-temperature microscopy method is performed. Based on the studies carried out in the CaO-P2O5 system, areas promising for the synthesis of materials have been identified that can be used for their technical and biological properties: 1) to correct bone tissue defects; 2) as inorganic fillers of hybrid organo-inorganic composite materials intended for the restoration of articular cartilage; 3) for gluing bone fragments and filling cavities of pathological origin; 4) to replenish the mineral composition of bones and tooth enamel. Keywords: synthetic nanocrystalline materials; phase diagram; the CaO-P2O5 system; the kinetics of formation; high temperature microscopy; correction of skeletal disorders.